Mechanism analysis of foam penetration in EPB shield tunnelling with a focus on FER and soil particle size - He Huang; Quan Sun; Tao Xu; Wanhuan Zhou (Underground Space, 2024)
Parameters of foam penetration in earth pressure balance (EPB) shield tunnelling, such as permeability coefficients and penetration distances, significantly impact tunnel face stability. However, existing studies have faced inaccuracies in analysing these parameters due to imitations in experimental methods. This study addresses this issue by employing enhanced methods for a more precise analysis of foam penetration. Experiments involving three distinct sand types (coarse, medium, and fine) and three foam expansion ratios (FER) (10, 15, and 20) are conducted using a modified model test setup. Benefiting from a novel computer vision-based method, the model test outcomes unveil two distinct foam penetration paths: liquid migration (Lw) and bubble migration (Lf). Three penetration phases — namely, injection, blockage & drainage, and breakage — are identified based on Lw and Lf variations. The initial “injection” phase conforms to Darcy's law and is amenable to mathematical description. The foam with FER of 15 has the maximum viscosity and, hence the Lf and permeability in the penetration tests with FER of 15 are the lowest in the same sand. The bubble size distribution of foam with different FER shows minor differences. Nevertheless, the characteristics of foam penetration vary due to the distinct particle size distribution (PSD) of different sands. Foam penetration creates low-permeability layers in both medium and fine sands due to the larger bubble size of the foam compared to the estimated pore sizes of medium and fine sands. While the coarse sand results in a different situation due to its large pore size. The distinctive characteristics of foam penetration in different sand strata are notably shaped by FER, PSD, and pore size distributions. These insights shed light on the complex interactions during foam penetration at the tunnel face, contributing valuable knowledge to EPB shield tunnelling practices.